Fundamental Methods in Drug Permeability, pKa, LogP and LogDx Determination - Mtewa, Andrew G; Ngwira, Kennedy; Lampiao, Fanuel; Weisheit, Anke; Tolo, Cassim U; Ogwang, Patrick E; Sesaazi, Duncan C (Journal of Drug Research and Development, 2018)
Potential drug molecular leads from plants are usually tested for their efficacy in bioactivity assays in preclinical trials. This is followed by testing for the properties of the molecular structures, if they can be bio-available to biological targets, should they proceed to clinical trials. Most drug molecules with proven bioactivities fail to qualify as potential drug candidates due to their poor molecular drug-like properties. It is therefore imperative for drug developers and discoverers to start focusing on the molecular structural properties at an early stage to decide whether the particular drug molecule, with bioactivity, is worthy investing on. This review aims at putting together and discussing fundamental methods for selected drug-like properties; permeability, pKa, LogP and LogDx. It was noted that basic methods on the aforementioned procedures are being customized for simplicity and convenience, mainly in the form of commercial in silico innovations. There is a need for cheaper methods to be developed to ease budgetary constraints on drug discovery and designing. This report will provide pointers to choose appropriate methods in drug designing and development, making the whole process more convenient and relatively cheaper for researchers, students and research funding bodies. Due to technical variations that each method has, reporting of results on these properties should be reported along with specific methods and conditions used.
Keywords: Permeability; pKa; LogP; LogDx; Drug development; Drug designing